14‐1: Large‐Area Processing of Solution Type Metal‐Oxide in TFT Backplanes and Integration in Highly Stable OLED Displays. Issue 1 (May 2017) - Marinkovic, Marko; Takata, Ryo; Neumann, Anita; Pham, Duy Vu; Anselmann, Ralf; Maas, Joris; van der Steen, Jan-Laurens; Gelinck, Gerwin; Katsouras, Ilias
Abstract : Solution type metal‐oxide semiconductor was processed on mass‐production ready equipment and integrated in a backplane with ESL architecture TFTs. Excellent thickness uniformity of the semiconductor layer was obtained over the complete Gen1 glass substrate (320 mm x 352 mm), resulting in homogeneous TFT performance and bias stress reliability. An 85‐ppi QVGA AMOLED display is demonstrated.